The effect of l‐carnitine supplementation on serum levels of omentin‐1, visfatin and SFRP5 and glycemic indices in patients with pemphigus vulgaris: A randomized, double‐blind, placebo‐controlled clinical trial. (18th December 2019) - Sepandar, Farnaz; Daneshpazhooh, Maryam; Djalali, Mahmoud; Mohammadi, Hamed; Yaghubi, Elham; Fakhri, Zahra; Tavakoli, Hajar; Ghaedi, Ehsan; Keshavarz, Ali; Zarei, Mahnaz; Shahrbaf, Mohammad Amin; Ghandi, Narges; et al.
Abstract: Pemphigus vulgaris (PV) is a chronic autoimmune disorder with potentially fatal outcomes. The aim of this study was to investigate the effect of l ‐carnitine (LC) on secreted frizzled‐related protein‐5 (SFRP5), omentin, visfatin, and glycemic indices in PV patients under corticosteroid treatment. In this randomized, double‐blind, placebo‐controlled clinical trial, 52 patients with PV were divided randomly into two groups to receive 2 g of LC or a placebo for 8 weeks. Serum levels of SFRP5, omentin, visfatin, and also glycemic indices were evaluated at the baseline and end of the study. LC supplementation significantly decreased the serum level of visfatin (95% CI [−14.718, −0.877], p = .05) and increased the serum levels of SFRP5 (95%CI [1.637, 11.380], p < .006) and omentin (95% CI [9.014, 65.286], p < .01). However, LC supplementation had no significant effects on the serum levels of glycemic factors such as insulin (95% CI [−1.125, 3.056], p = .426), fasting blood sugar (95% CI [−4.743, 3.642], p = .894), homeostatic model assessment of insulin resistance (95% CI [−0.305, 0.528], p = .729), and quantitative insulin‐sensitivity check index (95% CI [−0.016, −0.010], p = .81). LC supplementation decreased visfatin serum level and increased omentin‐1 and SFRP5 serum levels in patients with PV. However, it has no significant effect on the serum levels of insulin and glycemic indices.